Study guide for maternal-child nursing - McKinney, Emily Slone (Philadelphia, Pennsylvania : Elsevier Science, 2013)
Specially designed to parallel the material in Maternal-Child Nursing, 4th Edition, this user-friendly study guide provides valuable review of essential concepts and skills. Hands-on learning exercises and practical activities allow you to apply your knowledge to real-world scenarios.